The Digital Divide in Health-Related Technology Use: The Significance of Race/Ethnicity. (17th November 2018) - Mitchell, Uchechi A; Chebli, Perla G; Ruggiero, Laurie; Muramatsu, Naoko
Abstract: Background and Objectives: Technology can enhance the health and quality of life of diverse populations and may play an important role in reducing health disparities. Although a "digital divide" between the young and the old has been noted, it is unclear whether the use of technology for managing health differs by race/ethnicity among older adults. This study uses nationally representative data from community-dwelling older Americans to characterize racial/ethnic differences in health-related technology use. Design and Methods: Data came from 1, 336 white, black, and Hispanic adults aged 54 and older who completed the 2014 technology module of the Health and Retirement Study. Racial/ethnic differences in overall health-related technology use were assessed using Poisson regression. Then, F -tests were used to assess differences in the use of phone calls, text messages, E-mails, social media, health management sites, health-related mobile applications, web searches, and brain games for health purposes. Results: Compared to whites, older blacks and Hispanics were less likely to use technology for health-related purposes after accounting for demographic characteristics, education, and health conditions. They were also less likely to make or receive phone calls, use health management sites, search the web for health information, and use brain games for their health. Discussion and Implications: Older racial and ethnic minorities are less likely than whites to use certain technologies when managing their health. These findings highlight the importance of understanding the patterns of health-related technology use across racially and ethnically diverse populations to appropriately tailor interventions aimed at improving minority health and eliminating health disparities.